A Knowledge-based system for semiconductor wirebonding process and machine troubleshooting - Chung, Kok Wah. (2009)
Determining the root cause of machine/process failure plays a critical role in machine uptime and utilisation which directly impacts productivity. Rapid, accurate diagnosis is key to determining the root cause of failure. This Wirebonding Diagnostic Assistant (WBDA) is used to diagnose both process and machine related problems and also act as a training system for the wire bonding process. This WBDA is able to advise the technical support staff in the troubleshooting of six major thermosonic wirebonding process problems, namely golf ball, broken stitch, irregular wire loop, lifted stitch, cratering and non-sticking problems. It is also able to allow the user to enter the symptoms observed and find for possible/potential faults that are arising.